Imagenological diagnosis of obliterated ducts: a review. - Morales-González, Francisco Javier (2020)
Radiographic examinations are very useful for endodontists to diagnose and plan efficient treatment for their patients. Until recently, 2- dimensional projections, mainly periapical radiographs, were used for treatment planning of endodontic cases with obliterated canals. However, at present, the use of cone beam computed tomography (CBCT) is the most accurate tool and its use is increasingly more frequent, especially in cases of obliteration of the root canal. Image-guided endodontics has become an alternative procedure to conventional treatment, facilitating the treatment of partially or totally obliterated root canals. While there are still no data on any clinical technique able to determine the exact location of a calcified canal, the intraoperative use of CBCT in very complicated endodontic cases can help endodontists obtain a more accurate diagnosis to perform the most adequate procedure and, thereby achieve more successful treatment outcomes. The preservation of the structure and long-term retention of the tooth is essential after endodontic treatment and the use of image-guided endodontics considerably reduces iatrogenic lesions with fewer complications during the localization of site of obliteration in the root canal. Thus, the objective of this review was to describe the state of the art in the imaging diagnosis of obliterated ducts.